PENGARUH PROFESIONALISME DAN KEDISIPLINAN TERHADAP KINERJA GURU DIMEDIASI OLEH MOTIVASI PADA MADRASAH IBTIDAIYAH NEGERI KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Putri Retno Jenita; Elfiswandi; Zefriyenni (Journal Publicuho, 2025)
This study aims to examine the effect of professionalism and discipline on performance mediated by motivation. A quantitative approach with a hypothesis testing technique was used in this study. There were 90 samples with a random sampling technique, namely the teachers of the State Madrasah Ibtidaiyah in Bayang District, Pesisir Selatan Regency, West Sumatra. Data were collected through online questionnaire distribution and processed using SmartPLS 3.0 software with structural equation modelling techniques. The results showed that professionalism and discipline each had a positive and significant effect on work motivation. Professionalism, discipline, and motivation each have a positive and significant effect on performance. Motivation significantly mediates the relationship between professionalism and performance and the relationship between discipline and performance. The implications of the study emphasise the importance of maintaining the commitment and morale of teachers in educational institutions to provide the best teaching to students.